Mutational signatures in tumours induced by high and low energy radiation in Trp53 deficient mice - Yun Rose Li (Nature Portfolio, 2020)
Mutational signatures induced by ionising radiation remain largely unexplored. Here in TP53 mutant mice, the authors characterise the genomic landscape of tumours induced by high- and low-energy radiation.